Efficacy of Bracket Adhesive Remnant Removal by a Fluorescence-Aided Identification Technique with a UV Light Handpiece: In Vitro Study - Sabrina Elise Moecke; Pedro Caio Alves Barros; Adrielle Caroline Moreira Andrade; Alessandra Bühler Borges; César Rogério Pucci; Carlos Rocha Gomes Torres (Hindawi Limited, 2022)
Objective. This study aims to analyze the fluorescence-aided identification technique efficacy on adhesive remnant removal from the enamel surface after orthodontic bracket debonding. Materials and Methods. Forty-five extracted human upper central incisors were divided into 3 groups (n = 15) according to the kind of adhesive for bracket bonding and the use or absence of near UV light for remnant removal: BF/UV- fluorescent adhesive/UV light, BF/0-fluorescent adhesive/no UV light, and TB/0-nonfluorescent adhesive/no UV light. For all teeth, 100% of the adhesive used remained on the enamel surface after debonding. Fifteen dentists performed adhesive removal on the enamel surface using a carbide bur. The specimens were analyzed by a stereomicroscope, and the adhesive remnant percentage from each specimen was calculated. The time used by each dentist to perform the removal was recorded. The data were analyzed by one-way ANOVA and Tukey's test. Results. Significant differences were observed among groups for adhesive remnant (p=0.0008) and for time (p=0.0001). The means of adhesive remnant were BF/UV (5.84), BF/0 (34.37), and TB/0 (37.02). The mean times necessary to remove adhesive were BF/UV (1 min 40 s), BF/0 (3 min 03 s), and TB/0 (2 min 46 s). For the BF/UV group, significantly lower values of adhesive remnants and time for debonding were found (p<0.05). Conclusion. The fluorescence-aided identification technique significantly reduced the amount of adhesive remnant, and the time necessary to perform this clinical procedure.